The double‐edged sword of Tregs in M tuberculosis, M avium, and M. abscessus infection. Issue 1 (12th March 2021) - Verma, Deepshikha; Chan, Edward D.; Ordway, Diane J.
Abstract: Immunity against different Mycobacteria species targeting the lung requires distinctly different pulmonary immune responses for bacterial clearance. Many parameters of acquired and regulatory immune responses differ quantitatively and qualitatively from immunity during infection with Mycobacteria species. Nontuberculosis Mycobacteria species (NTM) Mycobacterium avium‐ (M avium), Mycobacterium abscessus‐(M abscessus), and the Mycobacteria species Mycobacterium tuberculosis‐(Mtb) . Herein, we discuss the potential implications of acquired and regulatory immune responses in the context of animal and human studies, as well as future directions for efforts to treat Mycobacteria diseases.